Islamic Fanatism and Terrorism Cases in Indonesia the Perspective of Islamic Criminal Law - Ahmad Kamaludin; Iskandar Iskandar (Institut Agama Islam Negeri Palangka Raya, 2022)
Acts of terrorism are often associated with Islamic teachings, which lead to a bad stigma against Islam. Cases of terrorism in Indonesia occur almost every year, which the shocking case of terrorism is the Bali bombing which killed 202 foreigners. The research aimed to analyze the problems of Islamic fanaticism and terrorism in Indonesia from the perspective of Islamic criminal law. The research used descriptive analysis, with the type of normative juridical research. The approach was historical and conceptual. The study showed that acts of terrorism defending Islam cannot be justified because terrorism has political intentions. Islam is a religion of raḥmatan lil ‘Ālamīn which loves good and hates evil. The government’s efforts to mitigate acts of terrorism in Indonesia are by making preventive efforts in the form of legal protection for someone suspected of adhering to terrorist radicalism. Prevention efforts are intended for, national preparedness, counter-radicalization, deradicalization, and fostering religious insight. In addition, the efforts made are by giving the role of society and mass organizations to perform moral movements.